2016
DOI: 10.1007/s00192-015-2924-1
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal prolapse repair with or without a midurethral sling in women with genital prolapse and occult stress urinary incontinence: a randomized trial

Abstract: Women with occult SUI had a higher risk of reporting SUI after POP surgery compared with women without occult SUI. Adding a MUS to POP surgery reduced the risk of postoperative SUI and the need for its treatment in women with occult SUI. Of women with occult SUI undergoing POP-only surgery, 13 % needed additional MUS. We found no differences in global impression of improvement and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 32 publications
2
57
0
1
Order By: Relevance
“…Here, more complications were observed in the mid urethral sling group than in the control group (47% vs 17%; RR 2.73; 95%CI 1.35‐5.55). The difference was statistically significant in mild (26% vs 6%; RR 4.01; 95%CI 1.20‐13.41), but not in moderate (14% vs 6%) and severe (7% vs 4%) complications . Interestingly, in this multicentre study which also assessed quality of life, there was no significant difference between the groups, although 13% of women in the occult stress incontinence group who did not have a continence procedure, eventually needed a further continence procedure .…”
Section: How Can Women Be Assessed To Determine the Chances Of Sui Afmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, more complications were observed in the mid urethral sling group than in the control group (47% vs 17%; RR 2.73; 95%CI 1.35‐5.55). The difference was statistically significant in mild (26% vs 6%; RR 4.01; 95%CI 1.20‐13.41), but not in moderate (14% vs 6%) and severe (7% vs 4%) complications . Interestingly, in this multicentre study which also assessed quality of life, there was no significant difference between the groups, although 13% of women in the occult stress incontinence group who did not have a continence procedure, eventually needed a further continence procedure .…”
Section: How Can Women Be Assessed To Determine the Chances Of Sui Afmentioning
confidence: 70%
“…Therefore, Borstad et al assessed women in a randomized study with SUI, 3 months after prolapse repair and found 29% had no SUI, and a further 13% declined a tension free vaginal tape . However, a longer follow up of a year led to 52% of women having symptomatic SUI after prolapse surgery compared to only 14% of women who underwent a midurethral tape at the same time with a vaginal prolapse repair . The only other study by Costantini et al only involved 23 women in each arm although the follow‐up was 5 years .…”
Section: Ici‐rs 2015 Proposal Groupmentioning
confidence: 99%
“…Concurrent MUS insertion was also associated with a higher risk of postoperative voiding dysfunction (OR 3.1) . Although prolonged bladder catheterization and short term voiding dysfunction seems to be higher in women undergoing prolapse surgery with MUS compared to prolapse surgery only, there is strong evidence that long‐term voiding dysfunction is comparable …”
Section: Discussionmentioning
confidence: 99%
“…The CUPIDO‐1 trial aimed at women with prolapse and co‐existing SUI . In the CUPIDO‐2 trial continent women with occult SUI were randomized and women without occult SUI were followed in a parallel cohort . Women were included between 2007 and 2014 in 13 centers across the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation